Reproductive Competition and Success in a Joint-Nesting Cuckoo - Robertson, Joshua K (My University, 2016)
Joint-nesting species experience complex and diverse social environments which can influence individual reproductive success. When social groups are formed by non- relatives, competition for representation in incubated clutches can be intense and result in substantial reproductive losses. Because conflicts of this nature have direct impli- cations on fitness, resolutions and outcomes of such are of particular interest to evolu- tionary research. For this reason, I explored patterns of reproductive competition and skew in joint-nesting Smooth-billed Anis (Crotophaga ani). In chapter I, I show marked differences in multivariate bill and body size between sexes of Smooth-billed Anis (Cro- tophaga ani) despite reportedly reduced sexual dimorphism in co-operative breeders. I also show that multivariate bill size in males correlates with annual reproductive success and individual contribution to clutches from multiple parents. A similar trend is not observed in females, suggesting potential for sexual selection on male bill size. Together, these data provide evidence for morphological influences on reproductive fitness in joint- nesting species. In chapter II, I show that relative parental effort is positively correlated with reproductive fitness in social groups of Smooth-billed Anis. Nocturnal incubation is risky and is biased toward a single male - akin to Groove-billed (Crotophaga sulcirostris) and Greater Ani (Crotophaga major). I report heightened reproductive contribution by nocturnally incubating males when compared to other males within social groups. In chapter III, I tested whether social group size is correlated with endocrine markers of stress in adult male and female Anis. Using a novel enzyme linked immunosorbent as- say, I show that corticosterone (the primary glucocorticoid in birds) deposited in feathers is highest in birds from atypically large social groups. While the direct consequences of elevated corticosterone on reproductive fitness in Anis is yet unknown, these results suggest that breeding in large social settings is likely to be physiologically expensive.
Keywords: Co-operative Breeding; Reproduction